Evaluation of Cervical Cytology Reports of Women screened by a Non-governmental Organization in Rivers State, Nigeria - D. A. Okoh; R. S. Iwo–Amah; N. C. T. Briggs; I. S. Musa; U. C. Oguzor (New Advances in Medicine and Medical Science Vol. 6, 2023)
According to World Health Organization (WHO) an estimated 570,000 new cases and 311,000 deaths from cervical cancer occurred in 2018 with 80-85% deaths taking place in developing countries. However, in the developed countries, through organized cervical cancer screening programs over 80% of mortalities are prevented annually. Across Nigeria, there were 14,943 new cases and 10,403 deaths in 2018. The high disease incidence and mortality rates are largely attributed to public unawareness, advanced disease stage presentation and inadequate screening programs including socio-cultural factors among others. Cervical cancer is a preventable genital tract malignancy if precancerous lesions are detected early and promptly treated. The aim of the study was to determine the incidence of precancerous lesions and highlight on the poor up take of cervical cancer screening. This study was conducted over eleven year period by Preventive Healthcare Initiative *PHI): a (Nongovernmental organization) during cervical cancer enlightenment campaigns. Conventional cytological screening was carried out on two hundred eligible women who consented to participate in the screening exercise, using the conventional George Papaniolaou method. The information was analyzed by simple statistical method. Two hundred cytology results of the women aged between 25 and 73 years with over 90% within the reproductive ages (40 to 49 years) were analyzed. One hundred and sixty (80%) of the participants had never heard of cervical cancer while 196 (98%) were being screened for the first time. One hundred and ninety (85%) of the women were negative for precancerous lesions. Ten (5%) women had precancerous lesions, [8(4%) had Low Grade Squamous Intra-epithelial Lesion (LGSIL), 1(0.5%) had High Grade Squamous Intra-epithelial Lesions] and 1 (0.5%) had Atypical Squamous Cells of Undetermined Significance (ASCUS). The study found that just 80% of respondents had a poor understanding of cervical cancer, with the majority of them (95%) having undergone their first screening. There is a need for government and nongovernmental organizations to raise awareness and educate the general people about cervical cancer prevention in order to reduce disease mortality.